SURVEY OF TOURIST INTEREST IN THE NATURAL TOURISM OBJECT OF PUSRI LAKE RANAU, OKU SELATAN REGENCY - Mirna Taufik; Inggit Kartika; Monanisa Monanisa (Universitas Negeri Medan, 2022)
Tourist interest is the interest of someone who wants to take a trip to find out something unique in a place. Tourist interest is influenced by pull factors and push factors, in order to increase the number of tourists, especially those visiting the Pusri Lake Ranau Nature Tourism. The purpose of this study was to determine the interest of tourists in the Pusri Nature Tourism object, South OKU Regency. The research population is visitors who are in Pusri Nature tourism. The sample used is 44 respondents. This type of research is quantitative descriptive and the data collection techniques used are observation, questionnaires, and documentation. research data processing using descriptive statistics while the data analysis technique used is the percentage (%). The results showed that tourist interest in the Pusri Nature tourism object was dominated by female visitors, aged 16-25 years. For tourist interest in the Pusri Nature tourism object, it is relatively high at 75 percent. This can be seen from the tourist attraction factors in the form of tourist sites, comfort in traveling, beauty of tourist sites, tourist location facilities and accessibility of tourist sites.Keywords: Tourist Interest, Pusri Danau Ranau, South OKU